After Neoliberalism - Antonio, Robert J. (The Wiley-Blackwell Companion to Sociology, 2011)
This chapter contains sections titled: * Clashing Models of Capitalism: Hayek VS. Polanyi * Market Liberalism's Return: From the “Not Quite Golden Age” to the “Great U - Turn” * Hegemonic Neoliberalism: From Crest to Crisis to Emphatic Reassertion(?) * Capitalism at the Point of Inflection: Neoliberalism's Wake * Conclusion * References
Keywords: 2008 financial meltdown; HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Hayek's and Polanyi's classic texts; New Deal; The Great U-Turn; ascendant neoliberalism; cutting edge issues; great recession; hegemonic culture; neoliberalism; neoliberalism's wake; self-regulating market

Polanyi on Markets, Democracy and the Crisis of Liberalism - Ebner, Alexander (The Beginnings of Scholarly Economic Journalism, 2011)
Karl Polanyi, who was born in 1886 in Vienna and died in 1964 in Pickering, Ontario remains a most influential theoretical figure in the social sciences, in particular stimulating both analytical and policy-related concerns that are related with the new institutionalism in economics, sociology and political science. Polanyian insights on the political economy of economic development from an institutional perspective have persistently shaped a variety of discourses that range from the theory of the welfare state to research in comparative economic systems and economic anthropology. Polanyi’s “Great Transformation” may be singled out as a key contribution to both the domains of economic sociology and political economy, as it addresses basic tensions between the developmental dynamics of the market economy and the institutional substance of political democracy (Block 2001).
Keywords: crisis of liberalism; early writings; methodology; methodology of the social sciences

Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Keywords: capitalism; emancipation; feminism; gender; welfare state

Adventures of an Austrian Trio Abroad: The Influence of Schumpeter, Polanyi and Hayek in Turkey and the Dissemination of Their Work - Ozveren, Eyup (The Dissemination of Economic Ideas, 2011)
Keywords: Austrian; Keynesian; Keynesianism; evolutionary; general aggregative models: Keynes; history of economic thought; history of economic thought since 1925: historical; history of economic thought: individuals; institutional; post-Keynesian; role of economics; role of economists